Development the Hydrophobic Property of Polyvinyl Alcohol/Silicon Dioxide/Titanium Dioxide Nanocomposites for Self-Cleaning and Soil Stabilization - Rania F. Khedr; Mohamed Abd Elhady (Molecules)
This study focused on synthesizing polyvinyl alcohol (PVA) utilizing glutaraldehyde (GA) as a crosslinking agent and silicon dioxide (SiO2) nanopowder with titanium dioxide (TiO2) nanopowder to reduce or prevent the hydrophilic property of PVA. Integrating SiO2 and TiO2 into the PVA boosted the hydrophobicity, thermal properties, and self-cleaning of the PVA film. The characteristic properties of PVA/GA, PVA/SiO2/GA, and PVA/SiO2/TiO2/GA nanocomposites polymer membranes were investigated by gel content, swelling capacity, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction patterns (XRD), scanning electron microscope (SEM), thermal gravimetric analysis (TGA), and contact angle. The resulting PVA/5%SiO2/1%TiO2/GA nanocomposite exhibits much better physical properties than PVA/GA hydrogel (water absorbency from 3.1 g/g to 0.07 g/g and contact angel from 0° to 125°). In addition, the nanocomposite retains very low swelling properties. These prepared nanocomposites are promising in a variety of applications such as sand soil stabilizers, construction, and building works where they exhibit excellent water resistance performance. This study introduces a novel approach for creating hydrophobic polymeric membranes from hydrophilic polymeric materials to stabilize sandy soil effectively.